Equivalent model of thin-walled orthotropic composite plates with straight segments using variational asymptotic method. (1st March 2021) - Zheng, Shi; Yifeng, Zhong; Xiao, Peng; Qiushi, Luo
Highlights: The 2D-EPM of TW-OCP is established by using VAM, and verified by comparing with 3D-FEM. The local coordinate system and the constraints at intersections of each segment are introduced. The details of local field distribution within unit cell of TW-OCP are well captured. The geometry of longitudinal stiffeners has great influence on the equivalent stiffness. The DOFs of the 2D-EPM is greatly reduced, which has a high calculation efficiency. Abstract: Accurate and effective prediction of the static and dynamic behavior of thin-walled orthotropic composite plates (TW-OCP) is necessary in the preliminary design. Considering that the thickness of each segment of TW-OCP is relatively thin, the constitutive modeling of unit cell is carried out to obtain the constitutive relations by using variational asymptotic method, which can be used as effective properties of the two-dimensional equivalent plate model (2D-EPM). Furthermore, constraints are applied at the intersections of each segment to ensure the continuity of displacement and slope. Finally, the effects of different structural parameters on the equivalent stiffness and anisotropy are discussed, such as the layup configuration of the panel, the inclination angle and thickness of stiffeners, and the period length of unit cell. The results show that compared with the results from three-dimensional finite element model (3D-FEM), the 2D-EPM not only has high accuracy, but also greatly reduces the degree of freedom, which has a high computational efficiency. Geometric shape (mainly determined by the inclination angle of longitudinal stiffeners) is one of the main factors that determine the anisotropy and equivalent stiffness of TW-OCP. The established equivalent model provides a simple, quick, and comprehensive way for the design and optimization of TW-OCP.